2007
DOI: 10.1128/aem.02275-06
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-Oxidizing β-Proteobacteria from the Oxygen Minimum Zone off Northern Chile

Abstract: The composition of ammonia-oxidizing bacteria from the ␤-Proteobacteria subclass (␤AOB) was studied in the surface and upper-oxycline oxic waters (2-to 50-m depth, ϳ200 to 44 M O 2 ) and within the oxygen minimum zone (OMZ) suboxic waters (50-to 400-m depth, <10 M O 2 ) of the eastern South Pacific off northern Chile. This study was carried out through cloning and sequencing of genes coding for 16S rRNA and the ammonia monooxygenase enzyme active subunit (amoA). Sequences affiliated with Nitrosospiralike clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 57 publications
4
44
1
Order By: Relevance
“…In the same sense, our data suggests that the variety of micro niches at oxyclines could be determining the observed differences in the structure of nosZ-communities inhabiting the ULOMZ off Chile and Perú; because it was evident the presence and dominance of the T-RFs of 77-bp and 710-bp off Chile and not off Perú. Our results support the hypothesis of niche differentiation previously proposed for global data set of nirS and nirK communities (Jones & Hallin 2010), and for ammoniaoxidizing -proteobacteria (Molina et al 2007) and anammox bacteria (Galán et al 2009) in the ESPO, which, could be a strategy of nosZ-community to be metabolically versatile in the ULOMZ to participate in several biologically mediated transformations of nitrogen and other elemental cycles as it has been argued by other researchers ).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In the same sense, our data suggests that the variety of micro niches at oxyclines could be determining the observed differences in the structure of nosZ-communities inhabiting the ULOMZ off Chile and Perú; because it was evident the presence and dominance of the T-RFs of 77-bp and 710-bp off Chile and not off Perú. Our results support the hypothesis of niche differentiation previously proposed for global data set of nirS and nirK communities (Jones & Hallin 2010), and for ammoniaoxidizing -proteobacteria (Molina et al 2007) and anammox bacteria (Galán et al 2009) in the ESPO, which, could be a strategy of nosZ-community to be metabolically versatile in the ULOMZ to participate in several biologically mediated transformations of nitrogen and other elemental cycles as it has been argued by other researchers ).…”
Section: Discussionsupporting
confidence: 79%
“…Also, from a functional point of view, metatranscriptomic findings report the metabolic versatility of nitrifiers, archaea, anammox and denitrifiers type nirS, nirK and nosZ (Stewart et al 2012) in the area; and other studies indicated the co-occurring and activity of ammonia-oxidizing -proteobacteria, Nitrosospira spp. principally (Molina et al 2007) and nirS-denitrifiers (Castro-González et al 2005). These reports (with 16S RNA and functional genes) along with our results suggest that diverse microbial groups inhabit the OMZ in the ESPO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All but two of the 99% OTUs fell within the marine/estuarine Nitrosospira-like clade (for example, cluster B in Francis et al 2003) (Figure 1). This cluster consists of environmental amoA sequences from various marine environments (Francis et al, 2003;Bernhard et al, 2005;Molina et al, 2007;Kim et al, 2008;Mosier and Francis, 2008). The other two OTUs are closely related to cultured N. europea and environmental sequences from various environments such as the Baltic Sea water column and an ANAMMOX bioreactor (Kim et al, 2008;Bae H, Paul T and Jung JY, unpublished).…”
Section: Overall Aob Compositionmentioning
confidence: 99%